2018
DOI: 10.1002/joa3.12065
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes in transcatheter aortic valve replacement patients requiring pacemaker implantation

Abstract: BackgroundPermanent pacemaker implantation is the most common complication after Transcatheter aortic valve replacement (TAVR) and is associated with worse outcomes and mortality. However, its impact on quality‐of‐life (QoL) outcomes remains unknown.MethodsWe included 383 consecutive patients undergoing TAVR from January 2012 to 2016 who completed a baseline Kansas City Cardiomyopathy Questionnaire (KCCQ‐12) health survey. The clinical, laboratory, angiographic, QoL, mortality, and occurrence of poor outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Table 1 shows the baseline characteristics of the included studies. The 36 studies included a total of 55,851 patients in the final analysis, from 2005 to 2018 [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The mean age of the patients was 81.9 years, with a mean STS score of 8.3.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the baseline characteristics of the included studies. The 36 studies included a total of 55,851 patients in the final analysis, from 2005 to 2018 [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The mean age of the patients was 81.9 years, with a mean STS score of 8.3.…”
Section: Resultsmentioning
confidence: 99%
“…Our facility exclusively utilizes the balloon expandable delivery systems of the Edwards Lifesciences Sapien line of devices, for which prior studies have identified a lower risk of post-implant conduction defects (around 5%) when compared to self-expanding device delivery systems (around 12%-39%) [28]. Our cohort compared well to previously published cohorts, with 19 patients (4.97%) necessitated pacing therapy [29]. Baseline characteristics between study groups were non-significant based on t-test and chi-squared testing, with the exception of underlying conduction abnormalities.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies outside of the PARTNER and CoreValve cohorts have further established that TAVR patients experience significant gains in QoL and functional recovery, with older patients and those needing a permanent pacemaker seeing smaller improvements [32] , [33] . Recent meta -analyses have documented that HRQOL and functional capacity improve after TAVR, despite better baseline functioning in recent studies and that non-TF TAVR patients’ trajectories are similar to those of SAVR patients [34] , [35] .…”
Section: Resultsmentioning
confidence: 99%